Molt strategy and aging of Rufous-collared Sparrow (Zonotrichia capensis) in Bogotá, Colombia (2018)
Molting is an important process of birds’ natural history and learning about molt and plumage allows a better understanding of various aspects of birds’ life. In temperate zones, knowledge about molt strategy, type of plumage characteristics and their association with age are well documented. In contrast, knowledge about molt in Neotropical birds is not well developed. One species with numerous studies regarding molt in several localities is the widely-distributed Rufous-collared Sparrow (Zonotrichia capensis). These studies covered various localities along the species range, facilitating comparisons among populations, and providing an excellent model for the study of plumage and molt variation. In this study, I described both molt strategy and extent of molt Z. capensis costaricensis, through sampling data for one year at two localities in Bogotá city. I captured and banded Z. capensis individuals and collected information about characteristics such as molt limits, skull ossification and iris coloration, which allow for the identification of molt/plumage type and its relation to age categories of a cycle-based age classification system. I found that Z. capensis has a complex basic strategy, where all prebasic molts, including prejuvenal molt, are complete and the preformative molt is a partial molt. The results are congruent with previous findings for this species in some areas. Nevertheless, the molt varies largely in Z. capensis across its distribution and individuals out of Neotropics have an additional partial-incomplete prealternate molt and it is still unknown why.